ANALISIS DAMPAK PROGRAM PUPUK BERSUBSIDI TERHADAP PRODUKSI DAN PENDAPATAN PADA KELOMPOK TANI DI DESA MENAMING - Melda Yani; Arfianti Novita Anwar; Devi Novianti (Komunitas Manajemen Kompetitif, 2026)
The subsidized fertilizer program is a strategic government policy to increase agricultural productivity and farmer welfare through input cost efficiency. This study aims to analyze the impact of the subsidized fertilizer program on production levels and farmer incomes in farmer groups in Menaming Village. Respondents in this study were farmer groups (Gapoktan) comprising three groups: Jaya Makmur, Adil Makmur, and Jagoan Subur. The analytical method used was quantitative descriptive analysis, calculating total costs (Total Cost), total revenue (Total Revenue), net income, and farming efficiency using the R/C Ratio.The results showed that the average land ownership of the respondent farmers was 1.56 hectares, with an average productivity of 3,200 kg per hectare. The subsidized fertilizer program had a significant impact on production by ensuring the availability of nutrients at affordable prices for farmers. From an economic perspective, the use of subsidized fertilizer successfully reduced production costs to Rp 6,826,250 per hectare, resulting in a net income of Rp 1,000,000 per hectare. 13,013,750 per hectare with a selling price of Rp6,200/kg of unhusked rice. The R/C ratio obtained was 2.9, indicating that farming in Menaming Village is very feasible and profitable. The conclusion of this study is that the subsidized fertilizer program significantly increased production volume and farmer income in Menaming Village, although its effectiveness still needs to be supported by timely distribution.